Dampak Penanaman Pendidikan Kewirausahaan bagi Mahasiswa di Era Globalisasi - Lestari, Iis Dewi; Brahma, Ismail Akbar (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2023)
Entrepreneurship in Indonesia is still relatively low compared to other countries. According to the Badan Pusat Statistik (BPS) Indonesia, the number of educated unemployed individuals in Indonesia reached 6.27 million in August 2020, with these facts, it is high time for universities to instill and promote entrepreneurship massively among students. Through entrepreneurship education, it is hoped that a high level of interest in entrepreneurship will be cultivated among students. The objective of this study is to determine the impact of entrepreneurship education on students' interest in entrepreneurship at the globalization. The research used a qualitative descriptive method, involving the collection of necessary data through literature studies aimed at describing, explaining and analyzing facts and data obtained from previous articles and journals that support the research theme. The results of this research indicate that through the implementation of a flexible curriculum, entrepreneurship can be consistently integrated into all universities to stimulate students' interest in entrepreneurship.